Determinants of Reduced Genetic Capacity for Butyrate Synthesis by the Gut Microbiome in Crohn's Disease and Ulcerative Colitis. (9th October 2017) - Laserna-Mendieta, Emilio J; Clooney, Adam G; Carretero-Gomez, Julián F; Moran, Carthage; Sheehan, Donal; Nolan, James A; Hill, Colin; Gahan, Cormac G M; Joyce, Susan A; Shanahan, Fergus; Claesson, Marcus J
Abstract: Background and Aims: Alterations in short chain fatty acid metabolism, particularly butyrate, have been reported in inflammatory bowel disease, but results have been conflicting because of small study numbers and failure to distinguish disease type, activity or other variables such as diet. We performed a comparative assessment of the capacity of the microbiota for butyrate synthesis, by quantifying butyryl-CoA:acetate CoA-transferase [BCoAT] gene content in stool from patients with Crohn's disease [CD; n = 71], ulcerative colitis [UC; n = 58] and controls [ n = 75], and determined whether it was related to active vs inactive inflammation, microbial diversity, and composition and/or dietary habits. Methods: BCoAT gene content was quantified by quantitative polymerase chain reaction [qPCR]. Disease activity was assessed clinically and faecal calprotectin concentration measured. Microbial composition was determined by sequencing 16S rRNA gene. Dietary data were collected using an established food frequency questionnaire. Results: Reduced butyrate-synthetic capacity was found in patients with active and inactive CD [ p < 0.001 and p < 0.01, respectively], but only in active UC [ p < 0.05]. In CD, low BCoAT gene content was associated with ileal location, stenotic behaviour, increased inflammation, lower microbial diversity, greater microbiota compositional change, and decreased butyrogenic taxa. Reduced BCoAT gene content in patients with CD was linked with a different regimen characterised by lower dietary fibre. Conclusions: Reduced butyrate-synthetic capacity of the microbiota is more evident in CD than UC and may relate to reduced fibre intake. The results suggest that simple replacement of butyrate per se may be therapeutically inadequate, whereas manipulation of microbial synthesis, perhaps by dietary means, may be more appropriate.